2022
DOI: 10.3389/ijph.2022.1604769
|View full text |Cite
|
Sign up to set email alerts
|

Workplace Bullying and Violence on Burnout Among Bangladeshi Registered Nurses: A Survey Following a Year of the COVID-19 Pandemic

Abstract: Objectives: To investigate burnout among Bangladeshi nurses and the factors that influence it, particularly the association of workplace bullying (WPB) and workplace violence (WPV) with burnout.Methods: This cross-sectional study collected data from 1,264 Bangladeshi nurses. Mixed-effects Poisson regression models were fitted to find the adjusted association between WPB, WPV, and burnout.Results: Burnout was found to be prevalent in 54.19% of 1,264 nurses. 61.79% of nurses reported that they had been bullied, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(19 citation statements)
references
References 61 publications
0
18
0
1
Order By: Relevance
“…[ 27 , 30 34 , 39 – 41 , 43 , 48 , 50 , 52 , 55 , 58 , 59 , 61 , 67 , 68 , 72 , 73 , 76 82 , 84 86 , 91 93 , 95 , 96 ]…”
Section: Resultsunclassified
“…[ 27 , 30 34 , 39 – 41 , 43 , 48 , 50 , 52 , 55 , 58 , 59 , 61 , 67 , 68 , 72 , 73 , 76 82 , 84 86 , 91 93 , 95 , 96 ]…”
Section: Resultsunclassified
“…Studies have found that workplace violence triggered burnout among HPs ( 29 , 43 ). Saifur also found workplace violence-exposed nurses were at a greater risk of burnout during the COVID-19 pandemic ( 44 ). We also observed a positive association between workplace violence and burnout.…”
Section: Discussionmentioning
confidence: 99%
“…Cronbach's α coefficient ≥ 0.60 for each subscale indicated acceptable internal consistency. 28 Text-retest reliability was tested by Pearson's correlation coefficient ( r ), where a value of > 0.70 was considered acceptable. 29 …”
Section: Methodsmentioning
confidence: 99%